Management of early hepatocellular carcinoma: results of the Delphi consensus process of the Americas Hepato-Pancreato-Biliary Association. Issue 5 (May 2021) - Gholami, Sepideh; Perry, Lauren M.; Denbo, Jason W.; Chavin, Kenneth; Newell, Philippa; Ly, Quan; St. Hill, Charles; Morris-Stiff, Gareth; Kessler, Jonathan; Frankel, Timothy L.; Parikh, Neehar D.; Philips, Prejesh; et al.
Abstract: Background: There are many potential treatment options for patients with early stage hepatocellular carcinoma (HCC) and practice patterns vary widely. This project aimed to use a Delphi conference to generate consensus regarding the management of small resectable HCC. Methods: A base case was established with review by members of AHPBA Research Committee. The Delphi panel of experts reviewed the literature and scored clinical case statements to identify areas of agreement and disagreement. Following initial scoring, discussion was undertaken, questions were amended, and scoring was repeated. This cycle was repeated until no further likelihood of reaching consensus existed. Results: The panel achieved agreement or disagreement consensus regarding 27 statements. The overarching themes included that resection, ablation, transplantation, or any locoregional therapy as a bridge to transplant were all appropriate modalities for early or recurrent HCC. For larger lesions, consensus was reached that radiofrequency ablation and microwave ablation were not appropriate treatments. Conclusion: Using a validated system for identifying consensus, an expert panel agreed that multiple treatment modalities are appropriate for early stage HCC. These consensus guidelines are intended to help guide physicians through treatment modalities for early HCC; however, clinical decisions should continue to be made on a patient-specific basis.